The European Union in the Face of the Phenomenon of Relocation in the Process of Dustrialisation - Piotr WALĄG (Communications of International Proceedings, 2020)
In debates on economic development in developed countries, the subjects of wage inequality, unemployment and falling living standards are often associated with the process of deindustrialisation and the accompanying phenomenon of relocation. Although only undesirable effects of these phenomena are politically exposed, it is important to show their economically positive consequences. In particular, due to the high short-term costs of deindustrialisation processes and the phenomenon of relocations in certain areas, the need for an active role for the state emerges, for example, in shaping a policy of industrial transformation towards a modern economy and innovation.  The main aim of the article is to show deindustrialisation as a natural process of economic development and to take a critical look at the phenomena that accompany it, and particularly at relocations as part of the European Union's competitiveness policy.  The thesis of the article is that deindustrialisation and the associated phenomenon of relocation are desirable processes if economic development is to be marked by a transition towards economies with high levels of productivity and innovation. However, the EU's competitiveness policy should be conducive to this transformation.  The next parts of the article will show the process of deindustrialisation and the strongly related phenomenon of relocation, and then, using Eurostat statistics, will present the challenges facing EU economies as part of structural changes in industry and, in the final part, will highlight the opportunities and dangers arising from deindustrialisation and relocation which European Union policy faces.
Keywords: Relocation; Reallocation of Production Factors; Industrial Policy; Deindustrialisation; Competitiveness; Industrial Transformation; Innovation.